1999
DOI: 10.1021/es980500g
|View full text |Cite
|
Sign up to set email alerts
|

Public Participation and the Environment:  Do We Know What Works?

Abstract: This literature review of studies on public meetings, workshops, and community advisory committees discusses public participation based on empirical evidence. Public participation "success" is defined by researchers' criteria that are divided into two categories: (1) those that evaluate the success of the participatory process and (2) those that evaluate the success of the outcome of the process. We find the form of participationspublic meetings, workshops, or citizen advisory committeessdoes not determine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
307
0
17

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(330 citation statements)
references
References 27 publications
6
307
0
17
Order By: Relevance
“…To address this, recent authors have developed several frameworks to evaluate public participation effectiveness (e.g. Chess and Purcell 1999;Rowe and Frewer 2000;Stephens and Berner 2011).…”
Section: The Concept Of Public Participation Effectivenessmentioning
confidence: 99%
“…To address this, recent authors have developed several frameworks to evaluate public participation effectiveness (e.g. Chess and Purcell 1999;Rowe and Frewer 2000;Stephens and Berner 2011).…”
Section: The Concept Of Public Participation Effectivenessmentioning
confidence: 99%
“…3 The official PACT guidance documents [34,37] 4 that are disseminated to PSNI officers identify the PACT model as the 'minimum expected standard means of community engagement' for the PSNI. In this sense, PACT is promoted as 'neighbourhood focused' and 'neighbourhood owned' [37; 1], and as providing a mechanism that 'give[s] focus for identifying community concerns', thus 'encouraging communities and neighbourhoods to identify and solve problems alongside the PSNI ' [36; 12].…”
Section: The Structure Of Pact Partnershipsmentioning
confidence: 99%
“…In the end, however, the overall quality of environmental decisions should also be judged by both process (i.e., the steps in a structured, decision aiding approach) and outcomeoriented (i.e., decision makers' ability to utilize these steps effectively) attributes (35). We believe, therefore, that the disagreement observed in this study between decision makers' self-reported evaluations and their actual choice behavior, as well as the implications of this finding for the design of future environmental decision making efforts should not be ignored.…”
Section: Figure 1 Mean Funding Allocations Across Three Environmentamentioning
confidence: 99%